Use of cassava derivative in water based drilling mud - Samavati, Raheleh (2016)
Drilling mud is a mixture of clays, chemicals and water applied in the drilling operation. The mud is pumped down the drill hole to achieve various functions such as cooling and lubricating the drill bits, flushing out the cuttings and strengthening the hole stability. The use of drilling mud in oilfield is often challenged by a number of factors, which require mud to withstand extreme temperatures and pressure without losing its functional integrity. Due to their excessive polluting characteristic, they are subjected to increasing number of waste management regulation and reinforcement. Biopolymers such as starch from agriculture based are reported to be a good replacement, but hampered by their thermal instability and low shear tolerability. To date, none of these polymers can be used as fluid loss and temperature reducing agent in mud formulation. Besides, they also reportedly failed to function after one pass of mud circulation system. The use of biodegradable polymer is desirable due to their environmental friendly, non-toxic, cheap and easily available for industrial application.The objective of this study is to investigate and optimize starch from cassava as alternative option to a more expensive commercially applied starch counterpart, such as corn, potato and wheat. Various derivatives from cassava was used, namely ubi kayu,elubo garri (yellow garri), ijebu garri (white garri) and fufu. All the experiments were carried out according to the National Iranian South Oil Company and American Petroleum Institute Standards set for the actual oil-field drilling condition. The influence of starch modification and usage of carbon black and gilsonite as additives for thermal stability enhancement and fluid loss reduction of water based muds(WBM), in extreme drilling temperatures was also investigated.The WBM was prepared by suspending different starch in saturated salt water,followed by addition of weighting materials. The WBM samples were formulated in different mud weights (light average and heavy) intended for verious borehole sizes of an actual drilling operation set-up.The UBM samples were subjected to drilling environment by placing them in a hot rolling oven for 8hrs.Four sets of temperatures were used:200, 250, 275 and 300F. representing the actual drilling hole temperature.After the hot roll, fluid loss and rheological (plastic viscosity, yield point, apparent viscosity, gel strength (10s and 10min) properties of each WBM samples was analyzed. Results revealed that at temperatures of 200 and 250F,cassava derivatives used in light average and heavy mud weights of WMB formulations were acceptable as a fluid loss agent.However,the light weighted WBM formulation failed at higher temperature of 275F, unlike the average and heavy WBMs. At 300 F, all of them were rejected in all WBM weights formulations. Therefore, to improve the thermal stability and fluid loss control of cassava WBM at this temperature, starch was subjected to acid modification step prior to mud preparation. Results from the WBM containing modified starch showed insignificant improvement of the fluid loss property.Another option to enhance thermal stability of WBM at 300F was by adding thermal enhancer agent. In this study, carbon black (CB) and CB+ gilsonite blends were used as thermal enhance agents.Results showed,the addition of 1% CB and CB+ gilsolnite blends into the WBM formulation successfully reduce the fluid loss at 300 F,at 98% and 99%, respectively. The average WBM weight formulation with CB addition was qualified as a fluid loss agent, while in the heavy WBM weight samples, only fufu andubi kayu were qualified. When the mud was added with CB+ gilsonite, similar results were observed for light and average WBM weight formulations, whereas only ubi kayu and yellow garri were qualified in the heavy WBM weight formulations.Cassava derivatives showed its potential to be industrially applied as a fluid loss additive in WBM intended for the drilling well temperature of 250F. For extreme drilling temperature of 300F.te F, the addition of CB+ gilsonite to the WBM formulation successfully improved the fluid loss control to an acceptable range. The overall assessment among all the starches investigated showed that the ubi kayu presented a superior functionality as fluid loss agent in WBM formulations.In summary, all starches used in this study failed API Standard as fluid loss control agent in WBM. Temperature of water use in preparing mud base does not affect rheological properties of WBM. The rheological properties of cassava-WBM samples in various formulation differs when subjected to different drilling temperatures. The acid modification of cassava derivatives improved WBM performance at HTHP circumstances. The addition of carbon black and gilsonite to the WBM formulation,further enhanced the thermal stability and fluid loss control of WBM. In short, this study found that cassava derivatives exhibited commercial potential as fluid loss agent in WBM.